2005
DOI: 10.1128/jvi.79.12.7380-7388.2005
|View full text |Cite
|
Sign up to set email alerts
|

Universal Influenza B Vaccine Based on the Maturational Cleavage Site of the Hemagglutinin Precursor

Abstract: Conventional influenza vaccines can prevent infection, but their efficacy depends on the degree of antigenic "match" between the strains used for vaccine preparation and those circulating in the population. A universal influenza vaccine based on invariant regions of the virus, able to provide broadly cross-reactive protection, without requiring continuous manufacturing update, would solve a major medical need. Since the temporal and geographical dominance of the influenza virus type and/or subtype (A/H3, A/H1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 57 publications
(89 reference statements)
0
53
0
Order By: Relevance
“…About it a preclinical animal model conducted by Bianchi et al demonstrated that using HA0 precursor of the viral HA, epitope widely conserved, as vaccine antigen, high immunogenicity and reduction in viral replications in the lower respiratory tract can be obtained. 49 Alternative strategies demonstrating to improve immune response against influenza drifted strains are represented by adjuvanted vaccines and ID vaccines.…”
Section: New Potential Influenza Vaccine Optionsmentioning
confidence: 99%
“…About it a preclinical animal model conducted by Bianchi et al demonstrated that using HA0 precursor of the viral HA, epitope widely conserved, as vaccine antigen, high immunogenicity and reduction in viral replications in the lower respiratory tract can be obtained. 49 Alternative strategies demonstrating to improve immune response against influenza drifted strains are represented by adjuvanted vaccines and ID vaccines.…”
Section: New Potential Influenza Vaccine Optionsmentioning
confidence: 99%
“…This may be advantageous when considering epitopes to be included in an improved vaccine for influenza virus, since more than one HLA molecule can present the peptide. In addition, a peptide conjugate vaccine based on the fusion peptide of the precursor HA of the B virus was shown to elicit protection in mice against lethal challenge of various strains of influenza B virus and can potentially be extended to influenza A virus strains (7). It is also interesting to note that a B cell epitope (3) and an HLA-A2-restricted CD8 ϩ T cell epitope (32) have been previously described.…”
Section: We Established a Human Cd4mentioning
confidence: 99%
“…Many previous attempts to use M2, 48,49 HA, 50 and NP proteins 51 to achieve broad-spectrum protection against influenza have been made. However, these studies have relied on the generation of " universal " antibodies that cross-react against diverse influenza strains -an approach that has yet to be proven practical in diverse populations.…”
Section: Discussionmentioning
confidence: 99%